Answer:
conjunction
Step-by-step explanation:
Answer:
x = 3
Step-by-step explanation:
2x + 3 = 9
2(3) + 3 = 9
6 + 3 = 9
Hope this helps!
=)
Calculate the square root which is -7*6-(-2)*(-3) and then multiply the numbers which is -42+2*(-3) that equals -42-6 and your answer is -48
B and D because it doesnt matter how you write the equation you still get the same answer,
don't forget to rate my answer 5 stars and thank me
Answer:
2.802691 revolutions per second
Step-by-step explanation:
You can round to the nearest whole number making it 3 revolutions per second